Specification for harmonized system of quality assessment for electronic components. Semiconductor discrete devices. Blank detail specification. Voltage-regulator diodes and voltage-reference diodes, excluding temperature-compensated precision reference diodes. (15th September 1987) - British Standards Institution,
No abstract available